Operações de manutenção da paz nações unidas: reflexões acerca da multidimensionalidade sobre os casos de Timor Leste e Haiti - Barea, Leonardo de Souza (2021)
The peace operations of the United Nations (UN) as an object of study are in constant progress, causing the need for greater planning and understanding for their conduct. The multidimensional aspect of these actions is configured as the center of this development, since the change in the form of armed conflicts, mainly in the post-Cold War, urged new imperatives that traditional strategies were no longer able to cover. The present paper has as a general objective to identify and expose elements that characterize the UN peace operations as “multidimensional”, aiming to reflect, in particular, the cases of East Timor and Haiti. Through bibliographical research, this work is developed as a reflection that seeks to contribute to a greater effectiveness of the studies of peace missions through interdisciplinarity, with no aiming to seek answers and/or culprits for the success and/or failure at the different levels of analysis of the aforementioned missions.